Marketing Strategies and Creativity of MSMEs in Selling Mozzarella Corndogs - Nanang Supriyadi; Gilang Ramadhan; Hendry Kurniawan (PT. Hidayat Muda Intelektual, 2026)
This study aims to analyze the marketing strategies and creativity implemented by MSME (Micro, Small, and Medium Enterprises) actors in increasing sales of mozzarella corndog products in Pekanbaru City. Utilizing a qualitative approach and data collection through in-depth interviews with six business actors, this research thematically illustrates how elements such as pricing strategy, digital promotion, product innovation, packaging, and customer experience interact to form an effective marketing strength. Furthermore, the study examines in detail various internal and external factors influencing the success of these marketing strategies, including local market dynamics and the characteristics of the primary target consumers. The findings indicate that bundling strategies, visual content such as “cheese pull” videos, collaboration with local endorsers, as well as visually appealing booth and packaging designs significantly contribute to attracting attention and building customer loyalty. Additionally, the success of these strategies is supported by the utilization of social media as a two-way communication platform, enabling MSME actors to establish more personal and responsive interactions with consumers. These results underscore the importance of integrating creativity, digital technology, and emotional approaches in brand building and enhancing the competitiveness of culinary MSMEs in the current digital era. Moreover, this study highlights the need for capacity development among MSME actors to manage marketing aspects strategically and innovatively in order to face increasingly complex competitive challenges. This research offers both practical and theoretical contributions to the development of digital-based MSME marketing models and can serve as a reference for designing effective and sustainable micro-business mentoring programs at the local level.